2012
DOI: 10.1590/s1517-83822012000300049
|View full text |Cite
|
Sign up to set email alerts
|

Amylase production by endophytic fungi Cylindrocephalum sp. isolated from medicinal plant Alpinia calcarata (Haw.) Roscoe

Abstract: Amylases are among the most important enzymes used in modern biotechnology particularly in the process involving starch hydrolysis. Fungal amylase has large applications in food and pharmaceutical industries.Considering these facts, endophytic fungi isolated from the plant Alpinia calcarata (Haw.) Roscoe were screened for amylolytic activity on glucose yeast extract peptone agar (GYP) medium. Among thirty isolates of endophytic fungi, isolate number seven identified as Cylindrocephalum sp. (Ac-7) showed highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 10 publications
4
29
0
3
Order By: Relevance
“…From our laboratory, thirty isolates from Alpinia calcarata Roscoe were screened, of which the isolate Cylindrocephalum sp. gave maximum amylase activity [26]. Among 112 isolates, thirty one isolates have shown cellulolytic activity (27.67%) and the highest cellulolytic activity was demonstrated in Aspergillus sp from P. longum (Table-6).…”
Section: Discussionmentioning
confidence: 97%
“…From our laboratory, thirty isolates from Alpinia calcarata Roscoe were screened, of which the isolate Cylindrocephalum sp. gave maximum amylase activity [26]. Among 112 isolates, thirty one isolates have shown cellulolytic activity (27.67%) and the highest cellulolytic activity was demonstrated in Aspergillus sp from P. longum (Table-6).…”
Section: Discussionmentioning
confidence: 97%
“…Also, El-Banna et al [43] found that K m 415 values and V max of immobilized α-amylase were higher than free enzyme. ... [3] ... [2] ... [4] Page 36 of 44 A c c e p t e d M a n u s c r i p t …”
Section: Kinetic Studiesmentioning
confidence: 99%
“…The production media were also supplemented with either (0.1%, w/v) Na + , K + , Zn 2+ , Mn 2+ , and Co 2+ supplied in sulphate form while 0.1% FeNa-EDTA (ferric EDTA) was supplied as ethylenediamine-tetraacetic acid iron(III) sodium salt to determine the effect of metal ions. Mycelial biomass obtained from each of the treatments was expressed as dry weight after drying in a hot air oven at 80 °C for 16 h (Sunitha et al 2012). Protein content was measured according to the method described by Bradford (1976) using Bovine Serum Albumin (Sigma) as a protein standard.…”
Section: Methodsmentioning
confidence: 99%